2012
DOI: 10.1007/s00270-012-0418-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Reliability and Quality of Online Uterine Fibroid Embolization Resources

Abstract: The overall quality of websites for UFE is moderate, with important but not serious shortcomings. The best websites provided relevant information about the procedure, benefits/risks, and were interactive. DISCERN scores were compromised by sites failing to provide resources for shared decision-making, additional support, and discussing consequence of no treatment. JAMA benchmarks revealed lack of authorship and currency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Since then, the web has grown, information on the web has proliferated, and for many if not most patients, the web has come to be not only a useful alternative to books, but also the primary source for self‐searched medical information. Our study is thus a timely addition to the dermatologic literature and is congruent in scope to similar recent studies in other specialties …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Since then, the web has grown, information on the web has proliferated, and for many if not most patients, the web has come to be not only a useful alternative to books, but also the primary source for self‐searched medical information. Our study is thus a timely addition to the dermatologic literature and is congruent in scope to similar recent studies in other specialties …”
Section: Discussionsupporting
confidence: 86%
“…6 Some studies of web-based medical information have attempted to use standardized criteria to evaluate the quality of medical information. 7,8 For instance, the DISCERN criteria attempt to assess relevance, clarity, bias, and the quality of treatment descriptions by asking the rater to grade these on a numerical scale; the LIDA tool similarly assesses accessibility, usability, and readability by suggesting certain technical programming procedures and rules to maximize these features; and the JAMA benchmarks rate the transparency of authorship, attribution, disclosure, and currency. We sought to forgo use of these tools because our expert group deemed them to be blunt instruments that were too nonspecific for our purposes.…”
Section: O H S E D U C a T I O N O N T H E I N T E R N E Tmentioning
confidence: 99%
See 1 more Smart Citation
“…As more attention has been paid to the design of healthrelated websites, it is worth noting that design may not be a consistent indicator of information quality. For instance, several of the studies reviewed suggested that design factors, specifically aesthetics and page ranks in search engines, were not reliable predictors of a site's overall content quality (Chestnutt, 2002;Kaicker, Wu, & Athreya, 2012;Irwin et al, 2011;Perez-Lopez & Perez Roncero, 2006;Tan, Kostapanagiotou, & Jilaihawi, 2009;Zermatten, Khazaal, Coquard, Chatton, & Bondolfi, 2010). Over the last decade, the design community has devoted considerable effort to making sites appear credible in order to gain users' trust (Fogg, 2003).…”
Section: Quality and Evaluation Criteria And Indicatorsmentioning
confidence: 99%
“…Both are quite important, but more difficult to measure, as available tools tend to be much more subjective (31). Unfortunately, the literature in radiology in this regard is far less robust (32).…”
Section: Discussionmentioning
confidence: 99%